ANALISIS PENGUASAAN KONSEP DAN KETERAMPILAN BERPIKIR KREATIF SISWA SD MELALUI PROJECT BASED LEARNING - Wa Ode Lidya Arisanti; Wahyu Sopandi; Ari Widodo (EduHumaniora: Jurnal Pendidikan Dasar, 2017)
Abstract: Learning science is not just memorize the concepts, but learn how to process and mastery of the scientific attitude. Actually, learning is still centered on the teacher, so that students can develop the knowledge and skills of thinking. Knowledge and thinking skills students can experience a change in the proper way, one way that can be done by applying the model of project-based learning. This study aims to determine whether there is a difference mastery of concepts and creative thinking skills between classes that implement learning model project based learning and classroom rather than project-based learning on water recycling materials. The research design used in this study was Quasi Experimental Design devoted no pattern Nonequivalent Control Group Design This design consists of two groups: the experimental group and the control group. Furthermore, each class were given a pretest and posttest study with mastery test questions using the concept of multiple choice questions of 15 questions and test creative thinking skills with five essay questions on each test. Classroom learning experiment treated with a model project based learning and classroom learning with no control got projet models based learning. The results showed in general there are significant differences in mastery of concepts (p = 0.00) between the experimental class learning by applying the model of project-based learning in the learning process (the average N-gain = 0.477) in the medium category, with students learning by applying rather than project-based learning (the average N-gain = 0.290) in the low category. There is no difference in the ability to think creatively (p = 0.22) between the experimental class and control class, with an average N-gain the experimental class 0,075 while the control class is 0.060 which both are in the low category.